2013
DOI: 10.1136/jnnp-2012-304005
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent transient ischaemic attack and early risk of stroke: data from the PROMAPA study

Abstract: According to our results, multiple TIAs within 7 days are associated with a greater subsequent risk of stroke than after a single TIA. Nevertheless, we found no independent predictor of stroke recurrence among these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
2
26
0
2
Order By: Relevance
“…Moreover, our study showed that large artery atherosclerosis was strongly associated with the risk of very early new TIA or stroke. Other studies identified this mechanism as an independent risk factor for recurrence at 7 day follow-up [12,13]. Similarly, the risk of recurrence at 7 days in patients with ischemic stroke was shown to be higher for those with large artery atherosclerosis [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, our study showed that large artery atherosclerosis was strongly associated with the risk of very early new TIA or stroke. Other studies identified this mechanism as an independent risk factor for recurrence at 7 day follow-up [12,13]. Similarly, the risk of recurrence at 7 days in patients with ischemic stroke was shown to be higher for those with large artery atherosclerosis [14].…”
Section: Discussionmentioning
confidence: 95%
“…This choice was justified by the fact that it has been already well established that these patients are at high risk of early recurrence, and the decision-making about hospitalization is usually easy in routine practice [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Durante las últi mas décadas se han destinado enormes y esperan zadores esfuerzos en el tratamiento de la fase aguda del ictus isquémico para cambiar la historia natural de la enfermedad. La aprobación del tratamiento fibrinolítico dentro de las primeras cuatro horas y media del ictus, y la demostración de la seguridad y efectividad de las terapias mecánicas combinadas han revolucionado la actitud terapéutica en estos pacientes [25]. Sin embargo, más allá de la fase aguda existen ciertos aspectos que merecen tam bién atención y que mejoran el pronóstico y la cali dad de vida de estos pacientes, como el tratamiento rehabilitador, el tratamiento de prevención secun daria y el estado emocional.…”
Section: Introductionunclassified
“…11 In addition, aggressive medical therapy may reduce the risk of recurrent stroke. Various modalities are used to detect extracranial and intracranial large-vessel atherosclerotic stenosis, including ultrasound, magnetic resonance angiography, and CT angiography (CTA).…”
Section: Vascular Imagingmentioning
confidence: 99%